Impact analysis of street children empowerment program in the context of social inclusion - Bertone; Radyati, Maria R. Nindita (Journal of Gender Equality Disability Social Inclusion and Children, 2025)
Background: PT. PHE ONWJ has conducted various community development programs but has never evaluated the impact of these programs using the Social Return on Investment (SROI) framework. This study aims to analyze the impact of one such program, the Street Children Empowerment Program, using SROI in the Tanjung Priok District, DKI Jakarta. Previous research highlights the importance of measuring social value creation to ensure sustainable community development. Methods: This research employs a mixed-method approach, combining both quantitative and qualitative methods. Data were collected through interviews and questionnaires with 46 respondents. The outcomes were analyzed using the sustainability compass approach, focusing on four aspects: Nature, Economy, Society, and Wellbeing.  Findings: The SROI ratio was found to be positive at 1:7.94, with the economic aspect contributing the largest benefits. The most significant impact occurred in 2013, and the stakeholders who benefited the most were the Kumala Foundation. Conclusion: The study demonstrates a positive return on investment for the Street Children Empowerment Program, with a notable impact in economic outcomes. The Kumala Foundation emerged as the most significant stakeholder benefiting from the program.  Novelty/Originality of this article: This study is the first to apply the SROI framework in evaluating PT. PHE ONWJ's community development program, offering valuable insights into measuring social value and demonstrating the effectiveness of empowerment initiatives for street children.